The future of the subsurface chlorophyll‐a maximum in the Canada Basin—A model intercomparison. Issue 1 (11th January 2016) - Steiner, N. S.; Sou, T.; Deal, C.; Jackson, J. M.; Jin, M.; Popova, E.; Williams, W.; Yool, A.
Abstract: Six Earth system models and three ocean‐ice‐ecosystem models are analyzed to evaluate magnitude and depth of the subsurface Chl‐ a maximum (SCM) in the Canada Basin and ratio of surface to subsurface Chl‐ a in a future climate scenario. Differences in simulated Chl‐a are caused by large intermodel differences in available nitrate in the Arctic Ocean and to some extent by ecosystem complexity. Most models reproduce the observed SCM and nitracline deepening and indicate a continued deepening in the future until the models reach a new state with seasonal ice‐free waters. Models not representing a SCM show either too much nitrate and hence no surface limitation or too little nitrate with limited surface growth only. The models suggest that suppression of the nitracline and deepening of the SCM are caused by enhanced stratification, likely driven by enhanced Ekman convergence and freshwater contributions with primarily large‐scale atmospheric driving mechanisms. The simulated ratio of near‐surface Chl‐ a to depth‐integrated Chl‐ a is slightly decreasing in most areas of the Arctic Ocean due to enhanced contributions of subsurface Chl‐ a . Exceptions are some shelf areas and regions where the continued ice thinning leaves winter ice too thin to provide a barrier to momentum fluxes, allowing winter mixing to break up the strong stratification. Results confirm that algorithms determining vertically integrated Chl‐ a from surface Chl‐ a need to be tuned to Arctic conditions, but likely require little or no adjustments in the future. Key Points: Model simulations suggest the observed SCM deepening to continue in the future Differences in projected SCM deepening are caused by physical factors Algorithms for integrated Chl‐ a require Arctic setting, but little future change